In vitro acaricidal activity of traditionally used medicinal plant against southern cattle tick Rhipicephalus (Boophilus) microplus - AlFaleh, Faleh A. (Asian Journal of Pharmaceutics (AJP), 2025)
Rhipicephalus microplus ( Boophilus) is an economy damaging cattle pest, and conventional acaricides face issues like resistance and environmental toxicity. Sustainable alternatives are urgently needed. Objectives: The aim of the study is to determine the efficacy of crude Cassia auriculata flower extract in increasing the mortality and inhibiting the development of the tick at multiple life stages. Materials and Methods: The acaricidal potential of C. auriculata flower extract is evaluated against the southern cattle tick, R. microplus, by testing four concentrations (25, 50, 75, and 100 μg/μL) across all major tick life stages. Crude flower extract of C. auriculata is prepared and applied at concentrations of 25, 50, 75, and 100 μg/μL to eggs, larvae, nymphs, and adult ticks. Mortality and developmental inhibition were measured at each stage. Results: A clear dose-dependent response is observed. The lowest dose (25 μg/μL) caused only modest mortality, while 50 and 75 μg/μL resulted in significantly greater tick mortality. The highest concentration (100 μg/μL) produced nearly total mortality in all life stages, including eggs, larvae, nymphs, and adults. Conclusion: C. auriculata flower extract demonstrates substantial acaricidal efficacy, especially at 100 μg/μL, against all life stages of R. microplus. The findings support its potential in integrated pest management as an herbal, eco-friendly, and effective alternative to synthetic acaricides.